SAT0307 Impact of the modified rheumatic disease comorbidity index(MRDCI) on drug survival of first line anti-tnfΑ drugs in patents affected with psoriatic arthritis in real life setting. (12th June 2018) - Fornaro, M.; Venerito, V.; Cantarini, L.; Anelli, M.G.; Cacciapaglia, F.; Lopalco, G.; Lapadula, G.; Iannone, F.
Abstract : Background: Psoriatic Arthritis (PsA) is a chronic condition resulting in significant physical disability and, in many cases, accelerated mortality. Studies have shown that patients with PsA suffer also from associated comorbidities, including cardiovascular diseases, obesity and metabolic syndrome, diabetes, osteoporosis, malignancy and depression; these could also play a role in determining discontinuation from therapy, especially if anti-TNFα drugs are prescribed. Objectives: Our study's goal is to demonstrate the impact of comorbidities on drug survival of first line anti-TNFα treatment in a cohort of patients affected with PsA. Methods: We retrospectively assessed 208 patients, (136 female, 72 male) mean age (±SD) 51.35±12.34 years, fulfilling the CASPAR criteria for PsA who underwent first line anti-TNFα therapy in two centres for a mean duration of 23.34±15.50, from 2011 to 2016. Disease characteristics were registered at first entry. To evaluate the burden of comorbidities we used the modified Rheumatic Disease Comorbidity Index (mRDCI), 1 a validated score including lung illnesses, cardiovascular diseases, stroke, hypertension, gastrointestinal disorders, diabetes, fractures, depression, obesity, kidney diseases and cancer. The mRDCI was scored at baseline as well. Drug retention was analysed using Kaplan-Maier curves. Cox regression models were used to estimate the inference of mRDCI and several disease characteristics on drug discontinuation. Goodness of fit of the final model was assessed comparing Cox-Snell residuals to Nelson-Alen cumulative hazard function. Results: Drug persitence in first line therapy was significantly higher in patients with mRDCI <4 (70.43%) than in those with mRDCI ≥4 (45.45%). Compared to mRDCI ≥4, those with mRDCI <4 showed significantly higher drug survival rate (p=0.018). Multivariate Cox model showed that mRDCI ≥4 (HR 1.94) and female gender (HR 2.39) were strong predictors of drug discontinuation. Nelson–Alen hazard function followed very closely Cox-Snell residuals showed final model fitted well the data except for large values of time. Conclusions: This study shows that an high mRDCI at baseline negatively impacts the persistence on first line anti-TNFα treatment in patients affected with PsA in real life setting; hence Rheumatologists should take into account comorbidities in the management of PsA and in admninistering anti-TNFα therapy as these may condition the persistence on therapy. Reference: [1] Staetgens, et al. Content and construct validity of the Rheumatic Diseases Comorbidity Index in patients with gout. Rheumatology2015Sep;54(9):1659–1663. Disclosure of Interest: None declared